2005
DOI: 10.1631/jzus.2005.b1195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low-molecular-weight-heparin and unfractionated heparin for acute PTE

Abstract: Abstract:Objective: Acute pulmonary thromboembolism (PTE) is a serious high mortality pulmonary vascular disease whose effective treatment decreases morbidity and mortality. To determine if low-molecular-weight-heparin (LMWH) is clinically as efficient and safe as unfractionated heparin (UH) in patients with diagnosis of acute non-massive PTE, our study compares the efficacy, adverse effects and costs of LMWH and UH. Methods: One hundred and fourteen patients with non-massive acute PTE were randomly divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our finding of a higher incidence of re-occlusive disease in those receiving UFH is consistent with findings of a study performed by Robinson et al In this study the dose of UFH was found to be subtherapeutic 30% of the time [23]. Unlike some previous studies we found that there was a higher incidence of haematoma and death in the LMWH group than the UFH group [24][25][26]. A recent Cochrane review showed a higher risk of major bleeding in medical patients treated for DVT with UFH than LMWH, in line with our study [9].…”
Section: Journal Of Vascular and Endovascular Surgery Issn 2573-4482supporting
confidence: 92%
“…Our finding of a higher incidence of re-occlusive disease in those receiving UFH is consistent with findings of a study performed by Robinson et al In this study the dose of UFH was found to be subtherapeutic 30% of the time [23]. Unlike some previous studies we found that there was a higher incidence of haematoma and death in the LMWH group than the UFH group [24][25][26]. A recent Cochrane review showed a higher risk of major bleeding in medical patients treated for DVT with UFH than LMWH, in line with our study [9].…”
Section: Journal Of Vascular and Endovascular Surgery Issn 2573-4482supporting
confidence: 92%
“…Duplicates from these 2 searches were identified and discarded, leaving 4059 unique articles. Screening and study selection as described above resulted in the identification of 20 articles 2039 meeting the inclusion criteria (Figure 1). Two articles 29,32 reported data found in other included reports 31,34 and were not included in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…12 Studies with LMWH have demonstrated that it has similar morbidity and mortality outcomes to UFH in treating DVT and nonmassive PE. 4,14,15 The LMWH and UFH are the most common anticoagulants recommended for treating confirmed nonmassive PE in ACCP guideline in 2012. 3 Many studies showed that LMWH is an effective drug for nonmassive PE; however, the role of LMWH in therapy for patients with massive PE is unclear.…”
Section: Discussionmentioning
confidence: 99%